Trends in incidence and predictions of cutaneous melanoma across Europe up to 2015. (21st August 2013) - Arnold, M.; Holterhues, C.; Hollestein, L.M.; Coebergh, J.W.W.; Nijsten, T.; Pukkala, E.; Holleczek, B.; Tryggvadóttir, L.; Comber, H.; Bento, M.J.; Diba, Ch.S.; Micallef, R.; et al.
Abstract Background Melanoma is a significant health problem in Caucasian populations. The most recently available data from cancer registries often have a delay of several months up to a few years and they are generally not easily accessible. Objectives To assess recent age‐ and sex‐specific trends in melanoma incidence and make predictions for 2010 and 2015. Methods A retrospective registry‐based analysis was performed with data from 29 European cancer registries. Most of them had data available from 1990 up to 2006/7. World‐standardized incidence rates (WSR) and the estimated annual percentage change (EAPC) were computed. Predictions were based on linear projection models. Results Overall the incidence of melanoma is rapidly rising and will continue to do so. The incidence among women in Europe was generally higher than in men. The highest incidence rates were seen for Northern and north‐western countries like the UK, Ireland and the Netherlands. The lowest incidence rates were observed in Portugal and Spain. The incidence overall remained stable in Norway, where, amongst young (25–49 years) Norwegian males rates significantly decreased (EAPC −2.8, 95% CI −3.6; −2.0). Despite a low melanoma incidence among persons above the age of 70, this age group experienced the greatest increase in risk during the study period. Conclusions Incidence rates of melanoma are expected to continue rising. These trends are worrying in terms of disease burden, particularly in eastern European countries.